FRI0288 Thymic stromal lymphopoietin (TSLP) biological effects on human peripheral blood b lymphocytes in primary sjÖgren's syndrome. (12th June 2018) - Gandolfo, S.; Bulfoni, M.; Fabro, C.; Doriguzzi Breatta, E.; Quartuccio, L.; Di Loreto, C.; Cesselli, D.; De Vita, S.
Abstract : Background: Thymic stromal lymphopoietin (TSLP) is an epithelial lymphopoietic cytokine belonging to interleukin (IL)−7 family, acting as a B-cell growth factor. A pathogenetic role of TSLP in primary Sjögren's syndrome (pSS) and pSS-related B-cell lymphoproliferation has been recently indicated. 1 Objectives: to investigate the biological effects of TSLP on human peripheral blood B lymphocytes in pSS. Methods: Peripheral blood B lymphocytes from 15 pSS patients, stratified according to their lymphoproliferative status (fully benign, fbSS: n=5; myoepithelial sialadenitis, MESA: n=5; B-cell non-Hodgkin lymphoma, NHL: n=5) and from 5 healthy blood donors (HBDs) were isolated by immunomagnetic negative selection and cultured with three different stimuli: i) TSLP; ii) combination of TSLP and IL-4; iii) combination of CD40 functional grade monoclonal antibody and IL-4. B-cell activation status was evaluated by flow cytometry, by analysing the expression of surface IgM after stimulation. An ELISA assay was also performed to assess the immunoglobulins (Ig) production in the B-cell culture surnatants after the exposure to the three different stimuli. Results: peripheral blood B lymphocytes isolated from fbSS patients were significantly activated by the combination of TSLP and IL4 (p=0.0218), as well as by the classic co-stimulation of antiCD40 plus IL4 (p=0.044), but not when TSLP was used alone. This pattern of responsiveness was observed also in HBDs. By contrast, the peripheral B-cells of NHL pSS patients were significantly activated by the TSLP alone (p=0.0157), without the necessity of other additional stimuli. A similar response to TSLP alone was observed also in MESA B-cell cultures but with no significance. As concerns Ig production in culture surnatants of peripheral B-cells, in fbSS patients we observed a significant increase of Ig production both after the exposure to TSLP plus IL4 (p=0.0417) and after the stimulation with antiCD40 plus IL4 (p=0.0293), but not with TSLP alone. By contrast, TSLP alone induced Ig production both in MESA (p=0.0368) and in NHL peripheral B-cells (p=0.0268). Unexpectedly, the combined stimulus of TSLP plus IL4 did not produce any significant effect in both these subgroups, and was less effective than TSLP alone also in stimulating B-cell surface IgM expression. Conclusions: human peripheral blood B-cells from pSS patients showed an increased responsiveness to TSLP, however with significant differences. In HBDs and in fbSS, TSLP induced a significantly higher B-cell activation and immunoglobulin production only with the addition of IL4, whereas in NHL TSLP alone was sufficient. In addition, IL-4 co-stimulus induced a lower activation than TSLP alone in NHL. Overall, also functional tests support a role of TSLP as an important driver of B-cell stimulation and lymphoma progression in pSS. Interactions of TSLP with other B-cell stimulating factors also deserve particular attention. Reference: [1] Gandolfo S, et al. Thymic Stromal Lymphopoietin (TSLP) expression is associated with lymphoproliferation and lymphoma in primary Sjögren's syndrome.Arthritis Rheumatol. 2017;69(suppl 10). Disclosure of Interest: None declared